(untitled) (Indian Journal of Animal Production and Management, 2025)
The present study was conducted at institutional poultry farm of Krishi Vigyan Kendra, Nandyal District, Andhra Pradesh, India to evaluate the effects of dietary liquid distillery stillage (LDS) supplementation on the growth performance of the Rajasri chicks. A total of 60 one-week-old Rajasri chicks were divided into three groups, and each group supplemented a different dietary treatment: T0 (basal diet without antibiotic), T1 (70% basal diet + 30% LDS), and T2 (50% basal diet + 50% LDS).The results indicated significant differences in growth among the dietary treatments. The highest average feed intake was observed in T2across all four weeks. Similarly, T2 showed the highest average body weight gain, suggesting better growth compared to T0 and T1. Moreover, T2 consistently exhibited the lowest FCR across all four weeks, indicating better feed efficiency compared to the other treatments. On the other hand, T1 showed intermediate performance in all three parameters, while T0 had the least favourable outcomes. From the experiment, it was concluded that, the supplementation of LDS in the diet of Rajasri chicks at 50% have resulted in improved feed intake, body weight gain, and feed efficiency, indicating enhanced growth performance. These findings underscore the significance of optimizing feed formulations to support better growth and productivity in poultry production systemsto achieve optimal growth and profitability in poultry farming.